Impactos da pandemia da Covid-19 da gestão de resíduos recicláveis nos municípios de Belo Horizonte (MG), Curitiba (PR) e São Paulo (SP) - Protásio, Júlia Ramos (2022)
The spread of Covid-19 has limited the maintenance and development of various activities in the world. The population's participation in segregation and recycling in the recyclable solid waste sector is essential to promote conscious consumption, environmental preservation and income for recyclable collectors, especially in times of crisis. However, with the pandemic, this sector was directly impacted by the total or partial suspension of its activities, or by the influence on the amount of materials received and marketed. The general objective was to identify the impacts of the Covid-19 pandemic on the management of recyclable solid waste, between March 2020 and March 2022, in the municipalities of Belo Horizonte (Minas Gerais), Curitiba (Paraná) and São Paulo ( State of Sao Paulo). The methodology used in this research consisted of a bibliographic and documentary review on the subject, selection of case study objects, identification and systematization of recommendations to assess the quality of recyclable waste management, and their application in case studies. Among the results, it was possible to identify 20 recommendations, organized in the management groups of Planning, Socio-educational Actions and Management. The evaluation of the observations, based on the Likert scale (1, 3, 5), totaled indicators with scores from 20 to 100. The cities of São Paulo and Belo Horizonte reached 92 points, and Curitiba with 82 points. In the Planning axis, the initiatives with the greatest variation between capitals were those directly related to recyclable waste pickers, with São Paulo meeting all the recommendations. In the Socio-Educational Actions group, the only initiative not attended by Curitiba and São Paulo was the cleaning of Recyclable Waste after collection by the collectors. In the Management group, it was noticed that the capitals met most of the initiatives. The main conclusions were: the lack of a tool to evaluate the management of RRS in pandemic events, the existence of 3 municipalities that can serve as an experience to direct public policies in this sense, and the need for other public administrators to pay attention to the new adaptations of management of essential services in a pandemic situation.